THE HEBREW INSCRIPTIONS FROM SARDIS - Cross, Frank Moore (Harvard theological review, 2002)
The inscriptions in Hebrew found in the Sardis Synagogue are few and fragmentary in comparison with the rich deposit of Greek inscriptions. One may compare the coeval synagogue in Hammath-Tiberias with its similar proportion of Greek and Hebrew inscriptions—despite its Palestinian locale. The Hebrew inscriptions were found, save one, in the Synagogue near the southern shrine in the east side of the Main Hall, and originally, no doubt, were built into or attached to the walls of the Synagogue.See A. R. Seager, “The Building History of the Sardis Synagogue,” AJA 76 (1972) 432–33. The inscription from outside the Synagogue, the graffito of Shemaryah, was found in a fill north of the Expedition camp.